The Algorithm as an Architect of Anxiety: 'Lucid Dreaming' Content Precipitating Acute Somniphobia in a Preadolescent—A Case Report on the 'Digital Pathogen' Phenomenon and Culturally Responsive Mediation - Ni Wayan Saka Rahayu; Putu Risdianto Eka Putra (HM Publisher, 2025)
Introduction: The pervasive integration of digital media into pediatric life has shifted the clinical focus from screen time quantity to content quality. Emerging